A2-2: Improving Diabetes Management with Mindfulness-based Stress Reduction - Whitebird, Robin (Clin Med Res, 2014)
BACKGROUND/AIMS: Managing diabetes can be challenging and stressful for many people resulting in poor diabetes control and increased mental health issues such as depression and anxiety. METHODS: We conducted a pilot study of mindfulness-based stress reduction (MBSR), a combination of mindfulness meditation and gentle yoga, to look at whether it could help patients better manage their diabetes. We recruited 38 people with diabetes and 2 HbA1c values > 8 in the prior 18 months to complete a community-based MBSR course. Participants attended eight-weekly intervention sessions and participated in home-based MBSR practice. Surveys and HbA1c values were obtained at pre and post-intervention, Cohen’s-d statistic was estimated for survey outcomes. Pre-post change was evaluated using paired t-test. RESULTS: Participants were 31- to 78-years-old (M = 57), the majority were female (68 %), white (70%), employed, with some college education. Mean HbA1c pre-intervention was 9.18. Participants showed significant improvement in pre-post measures of HbA1c (change .73%, P = .000), overall mental health (Cohen’s-d .69, P = .001), stress (Cohen’s-d −.76, P = .001), depression (Cohen’s-d .62, P = .001), and anxiety (Cohen’s-d .66, P = .001). There was also improvement in two measures of diabetes management: Problem Area in Diabetes Questionnaire (Cohen’s-d −.71, P = .002) and the Diabetes Empowerment Scale (Cohen’s-d .80, P = .000). CONCLUSIONS: These results suggest that MBSR may offer a safe and effective method for helping people better manage diabetes and improve their mental health. Effect sizes were large and significant pre-post differences were found indicating that a larger clinical trial is warranted.